Seasonally Related Disruption of Metabolism by Environmental Contaminants in Male Goldfish (Carassius auratus) - Bottalico, Lisa N.; Korlyakova, Julia; Weljie, Aalim M.; Habibi, Hamid R (Frontiers in Toxicology, 2021)
Endocrine disrupting chemicals mimic or disrupt action of the natural hormones, adversely impacting hormonal function as well as cardiovascular, reproductive, and metabolic health. Goldfish are seasonal breeders with an annual reproductive cycle regulated by neuroendocrine signaling which involves allocation of metabolic energy to sustain growth and reproduction. We hypothesize that seasonal changes in physiology alter overall vulnerability of goldfish to metabolic perturbation induced by environmental contaminants. In this study, we assess effects of endogenous hormones, individual contaminants and their mixture on metabolism of goldfish at different reproductive stages. Exposure effects were assessed using 1H-NMR metabolomics profiling of male goldfish midbrain, gonad and liver harvested during early recrudescence (October), mid-recrudescence (February) and late recrudescence (June). Compounds assessed include bisphenol A, nonylphenol, bis(2-ethylhexyl) phthalate, fucosterol and a tertiary mixture (DEHP + NP + FS). Metabolome-level responses induced by contaminant exposure across tissues and seasons were benchmarked against responses induced by 17β-estradiol, testosterone and thyroid hormone (T3). We observe a clear seasonal dependence to metabolome-level alteration induced by hormone or contaminant exposures, with February (mid-recrudescence) the stage at which male goldfish are most vulnerable to metabolic perturbation. Responses induced by contaminant exposures differed from those induced by the natural hormones in a season-specific manner. Exposure to the tertiary mixture induced a functional gain at the level of biochemical pathways modeling over responses induced by individual components in select tissues and seasons. We demonstrate the importance of seasonally driven changes in physiology altering overall vulnerability of goldfish to metabolic perturbation induced by environmental contaminants, the relevance of which likely extends to other seasonally-breeding species.